Problematika Penggunaan Buku Panduan pada Kurikulum 13 dan Kurikulum Merdeka di SDN Kunciran 2 - Adinda Zahra Putri Nasution; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2023)
: The condition of Indonesian education which until now has not yet found its identity. Curriculum changes have continued to be made until now we have arrived at the independent learning curriculum. Various problems even began to be felt. This research is based on the implementation of the Merdeka curriculum and the 2013 curriculum for teachers at Kunciran 2 Elementary School, what problems teachers face and how to overcome them. The research method used is qualitative with a descriptive approach, and data collection techniques are interviews, observation and documentation. The results of data analysis showed that teachers' problems in implementing the Merdeka curriculum and curriculum13 lie in the planning of learning implementation, planning and assessment of learning. The aim of this research is to find out the problems found in textbooks at Kunciran 2 Elementary School. So that we can find out what problems occur and the need for evaluation.